The programme director and the Teaching Excellence Framework: How do we train the former to survive the latter? - Massie, Ruth (Wiley, 2018)
The programme director undertakes a key role within UK universities in linking the department, or school, directly with the student (Vilkinas & Ladyshewsky, 2012) and their experience of the university. The role is multi-faceted and complex with a number of competencies required to successfully undertake it. Furthermore, the UK’s Teaching Excellence Framework (TEF) was fully introduced in 2016 and utilises existing measures such as student satisfaction, retention rates and destination of leavers (HEFCE, 2016) as a proxy for teaching excellence. Many of these metrics are also part of the day to day concerns of programme directors within universities. This research surveyed 89 programme directors on the training they have received to carry out their role and how it links to the TEF outcomes. The paper argues that there is insufficient training for programme directors and an increase in training may have a beneficial outcome for a university’s TEF results.
Keywords: Programme Director; Course Director; Training; Teaching Excellence Framework; Teaching Excellence; Leadership